Search for lepton-flavour violation in high-mass dilepton final states using 139 fb −1 of pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Beyond Standard Model, Exotics, Flavour Physics, Hadron-Hadron Scattering.; Springer Open.